Contribution of the Activated mTOR-STAT3 Pathway to the Pathogenesis of Focal Cortical Dysplasia Type IIIa in Pediatric Patients through Astrocyte Proliferation Mediation - Wang, Jiangya; Wu, Jiang; Li, Yang; Lv, Yuanyuan; Zhang, Xinying; Kang, Lin (Current Molecular Medicine, 2025)
ObjectiveThe aim of this study was to detect the association between the mTOR-STAT3 pathway and focal cortical dysplasia type IIIa (FCD IIIa) in children.MethodsA retrospective review was conducted based on 26 pediatric patients diagnosed with FCD IIIa who underwent surgical intervention. These patients were selected from a cohort of 157 individuals presenting with temporal lobe epilepsy. For comparative analysis, a control group consisting of 5 children who underwent intracranial decompression was established. Immunohistochemistry, immunofluorescence, and western blot techniques were used to assess the expression levels of mTOR, P-mTOR, P-70s6k, STAT3, P-STAT3, and GFAP in brain tissue specimens obtained from the two groups.ResultsThe mTOR-STAT3 pathway exhibited activation in the FCD IIIa group (all p < 0.01). Additionally, immunofluorescence analysis revealed that cells positive for P-STAT3 were identified as astrocytes. Moreover, within the FCD IIIa group, there was a marked elevation in the expression of the mTOR-STAT3 pathway in the hippocampus compared to the brain cortex tissue.ConclusionThe mTOR-STAT3 pathway was demonstrated to be substantially associated with FCD IIIa in pediatric patients. The activation of the mTOR-STAT3 signaling pathway may contribute to the pathogenesis of FCD IIIa in pediatric patients by modulating the proliferation of astrocytes.
Keywords: focal cortical dysplasia IIIa